Perubahan Jumlah dan Jenis Leukosit pada Pengguna Rokok Elektrik - Perdina Nursidika (Meditory : The Journal of Medical Laboratory, 2019)
An examination of leukocytes count and type of 30 e-cigarettes smokers has been done. E-cigarettes are a substitute for tobacco cigarettes which are categorized as safer because of fewer toxins. But the nicotine content in cigarettes can affect the immune system which is related to the leukocytes count and type. This study aims to describe the leukocytes count and types of in e-cigarette smokers who have used more than one month. Methods of examination using haematology analyser and peripheral blood smear. The results showed that the leukocytes count in 1 sample was low, 4 samples were high, and 25 other samples were normal. For leukocytes types, in 14 samples showed a type of cell abnormality by showing an increase in the number of eosinophils, neutrophils, lymphocytes and monocytes. It can be concluded that there are abnormalities in leukocyte counts and changes in leukocyte cell types in e-cigarette users.